Distribution Map Analysis of Independent Living Skills through Rasch Model in Primary School Students - Mulyasari, Effy; Ali, Mohammad; Sukirman, Dadang; Hamzah, Rifqy Muhammad (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2024)
Independent living skills need to be mastered by every student both in dealing with everyday life and in the school environment in the 21st century. Students must be able to develop their life skills so they can be independent and develop optimally. This study aims to analyze the grouping of the level of choice of Independent Living Skills items in elementary schools based on the teacher's perception of students through a combination of the standard deviation value (SD) and the logit average value (Mean). The research was conducted on elementary school teachers in West Java. The analysis was carried out through the Rasch Model with the Winstep application. The results of this analysis can indicate that there are various levels of choice of Independent Living Skills items. The grouping is based on hard-to-select items with a logit value greater than +1SD; difficult categories with a logit value of 0.0 logit +1SD; easy-to-select categories 0.0 logit – 1SD; and it is very easy to select with a value smaller than -SD. From this study it can be concluded that the Independent Life Skills instrument items can identify various levels of student independence. This instrument can be used for initial semester assessments in